Women's Experiences of Living with Adenomyosis: A Scoping Review through the Lens of Levine's Conservation Model - Yayu Handayani (STIKep PPNI Jawa Barat, 2026)
Background: Uterine adenomyosis (UA) is a chronic gynaecological condition characterised by the presence of endometrial tissue within the myometrium, causing dysmenorrhoea, abnormal uterine bleeding, dyspareunia, infertility, and reduced quality of life. Although its physical and psychosocial burden is well recognised, women’s lived experiences have not been comprehensively synthesised using a nursing theoretical framework. Objective: To systematically identify, map, and synthesise evidence on women’s experiences of living with adenomyosis using Levine’s Conservation Model. Methods: A scoping review was conducted following the Joanna Briggs Institute (JBI) methodology and reported according to the PRISMA Extension for Scoping Reviews (PRISMA-ScR). Literature searches were performed in PubMed/MEDLINE, CINAHL Plus, and ScienceDirect, supplemented by grey-literature searching and hand-searching of reference lists. Eligibility criteria were developed using the Population–Concept–Context (PCC) framework. Data were analysed using inductive content analysis and deductively mapped to the four conservation principles of Levine’s Conservation Model. Results: Twelve sources met the inclusion criteria, comprising five primary empirical studies, four secondary or contextual sources, and three grey-literature patient narratives. Women with adenomyosis experienced multidimensional challenges across all four conservation domains. These included energy depletion caused by chronic pain and fatigue, structural compromise related to pelvic pain, dyspareunia, and infertility, threats to personal integrity arising from stigma and delayed diagnosis, and disruption of social integrity through impaired relationships, occupational limitations, and financial burden. Conclusion: Adenomyosis profoundly affects women’s physical, psychological, and social well-being across all four domains of Levine’s Conservation Model. This review provides a theory-informed framework to guide holistic nursing assessment and person-centred care while highlighting the need for further research on diagnostic experiences and nursing-specific interventions